Minecraft mega builds : massive builds that you can make yourself! - Hunt, James (James R.) (New York, NY : Scholastic Inc., 2022)
Introduces various players' level builds in the game of Minecraft.
Inside you will find: amazing creations and builds!; movie projects and survival maps!; loads and loads of ideas!; everything you need to get started!
7.4
3-6
IG1090L
Keywords: Minecraft (Game) -- Juvenile literature; Video games -- Juvenile literature; Minecraft (Game); Video games